Flexural performance of reinforced oil palm shell & palm oil clinker concrete (PSCC) beam - Huda, M.N.; Jumaat, Mohd Zamin; Islam, A.B.M.S. (Elsevier, 2016)
The recent trend of globalization has seen massive construction leading to the radical destruction of natural stone deposits. To meet the high demand of normal weight aggregate in the production of concrete is a vital issue for ecological imbalances. Solid waste management from the agricultural and manufacture industries is another environmental issue. An innovative solution to reduce the negative impact on the environment is the production of structural lightweight concrete from these solid waste. This paper presents the structural performance of singly reinforced oil palm shell and palm oil clinker concrete (PSCC) beam. The structural-grade lightweight aggregate concrete, PSCC has been produced from the combination of oil palm shell (OPS) & palm oil clinker (POC) which are an agricultural waste and a by-product of palm oil industry. The produced lightweight concrete has the compressive strength of 46 MPa. The experimental works have been conducted involving six singly reinforced beams of dimension 150 mm × 250 mm × 3300 with varying reinforcement ratios (0.70–1.26%). For each type of reinforcement ratio, two beams have been tested under four point bending until failure. The data presented in this paper include the mode of failure, moment capacity, deflection characteristics, cracking behavior and ductility indices. Although PSCC has a low modulus of elasticity, the moment capacity and the deflection of singly reinforced PSCC beams are acceptable as the span-deflection ratio satisfies the allowable limit provided by BS 8110. All PSCC beams show typical flexural performance and experiences ductile failure giving ample amount of warning before the failure. For the beams with higher reinforcement ratio, the deflections at service loads exceeded the limit, suggesting to increase the beam depths. The crack widths of PSCC beams at service loads ranged from 0.21 mm to 0.26 mm satisfying BS 8110 for durability aspects. The ultimate moments predicted using BS 8110 overestimates for the PSCC beams up to the reinforcement ratio of 1.26%. Therefore, 20% overall reduction is suggested in moment capacity calculation using BS 8110. Further investigation is recommended to understand the shear behavior of reinforced PSCC beam.